A practical approach to altitude training: where to live and train for optimal performance enhancement - Levine, B. D.; Stray-Gundersen, J. (International Journal of Sports Medicine, 1992)
Altitude training may improve performance by a number of mechanisms. Acclimatization may improve both oxygen delivery and extraction. Hypoxic exercise may increase the training stimulus thus magnifying the effects of endurance training. Conversely, high altitude decreases VO2max and reduces the workloads at which training occurs. At altitude, base training is performed at a slower velocity and lower oxygen uptake (lower absolute workload) compared to sea level, though heart rate is similar and lactate is higher (probably greater relative workload). Interval workouts are performed at a lower absolute workload at altitude and are associated with lower peak heart rates and blood lactate concentrations. Red cell volume is increased during altitude training, as long as iron stores are normal. We suggest that for performance at altitude, acclimatization and/or hypoxic exercise is preferable; for performance at sea level, living at altitude (acclimatization) with sea level training may be the optimal strategy. However neither approach is a substitute for a carefully designed training program including appropriate rest and nutrition.